(untitled) (Philosophy and Progress, 2022)
India has one of the most heterogeneous societies in the world. It is a multi-cultural, multi-linguistic, multi-ethnic and multi-religious country. Constitutionally, it is also a sovereign socialist secular democratic republic. But in recent times, Hindu nationalism or Hindutva has been dominant in shaping Indian politics. Hindutva, a shorthand of Hindu nationalism, is actually a politico-ideological device that appears to be disassociated from the spiritual roots of Hinduism and, to many, it is very much alike to the rise of political Islam. Although Hinduism is native to the Indian subcontinent, Hindutva as a political ideology is comparatively a recent phenomenon which creates a growing concern to the land since 1920s. India experienced the rise of Hindutva as a concrete political ideology in 1923 introduced by V. D. Savarkar as it starts to achieve its popularity since 1980s. Obviously it has many reasons. Hindutva is not a monolithic concept as it is generally perceived. Rather, its text, subtext and context had changed throughout the 20th century depending on the period and leadership. This article aims to analyze the trend of the development of Hindu Nationalism or Hindutva in India since its start in the 20th century through a historical lens. Philosophy and Progress, Vol#69-70; No#1-2; Jan-Dec 2021 P 211-241